Beverage Intake and Its Effect on Body Weight Status among WIC Preschool-Age Children - Andrea Charvet; Fatma G. Huffman (Journal of Obesity)
Given the prevalence and consequences of childhood obesity, efforts are being made to identify risk factors and design evidence-based interventions to reduce its impact. Food and beverage consumption habits are established early in life, making preschool-age children an important group to focus on. This cross-sectional study explored beverage intake and its association with body weight status among low-income preschool-age children enrolled in the Special Supplementation Nutrition Program for Women, Infants, and Children (WIC). Authorized representatives for children between the ages of 3 and 4.9 years were interviewed at WIC clinics in Broward County, Florida. Anthropometric data were collected from the WIC data system. The intake of sugar-sweetened beverages (SSB), particularly fruit drinks, was significantly higher in overweight/obese children when compared with their under/normal weight counterparts. Independent of body weight status, the preschool-age children were consuming on average over twice as much as the recommended intake of 100% fruit juice per day for that age group. Close to 80% of the overweight/obese children consumed low-fat or fat-free milk most often than any other type of milk. The intake of SSB was positively correlated with both the intakes of 100% fruit juice and milk, and negatively correlated with the intake of water. When body weight status, race/ethnicity, and intake of other beverages were held constant, SSB intake was positively associated with milk intake and negatively associated with water intake. Results from this study support the need to encourage water intake and discourage SSB intake in an effort to reduce the risk for overweight and obesity in WIC-participating preschool-age children. Emphasizing the need to follow the recommendation to limit 100% fruit juice intake to 4 to 6 oz. per day is important when counseling families with young children. Efforts to increase awareness of the health consequences associated with consuming high-fat milk should continue.